2010
DOI: 10.3389/fpsyg.2010.00154
|View full text |Cite
|
Sign up to set email alerts
|

Going, going, gone: characterizing the time-course of congruency sequence effects

Abstract: Performance on traditional selective attention tasks, like the Stroop and flanker protocols, is subject to modulation by trial history, whereby the magnitude of congruency (or conflict) effects is often found to decrease following an incongruent trial compared to a congruent one. These “congruency sequence effects” (CSEs) typically appear to reflect a mesh of memory- and attention-based processes. The current study aimed to shed new light on the nature of the attention-based contribution to CSEs, by characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
155
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(179 citation statements)
references
References 38 publications
16
155
8
Order By: Relevance
“…However, there is evidence that it is influenced by more automatic mechanisms. First, conflict adaptation is strongest at short interstimulus intervals (∼500 ms) and declines thereafter (36). Here, variance adaptation was observed to occur very rapidly, with maximal effects at prime-target intervals of < 200 ms, and some loss of statistical power by 500 ms. Second, simply cueing participants that a trial will be congruent has an additional facilitatory effect (37).…”
Section: Discussionmentioning
confidence: 92%
“…However, there is evidence that it is influenced by more automatic mechanisms. First, conflict adaptation is strongest at short interstimulus intervals (∼500 ms) and declines thereafter (36). Here, variance adaptation was observed to occur very rapidly, with maximal effects at prime-target intervals of < 200 ms, and some loss of statistical power by 500 ms. Second, simply cueing participants that a trial will be congruent has an additional facilitatory effect (37).…”
Section: Discussionmentioning
confidence: 92%
“…Previous research has shown that interference is smaller when trial N-1 is incongruent (known as a congruency sequence effect (CSE)). CSEs were calculated using the criteria employed by Egner et al (2010), excluding the first trial from every block and any trials on which the word or response on trial N-1 was repeated on trial N, which left 27.8% of data for the analysis. We compared the magnitude of Stroop interference from trials that followed a neutral trial to Stroop interference from trials that followed an incongruent trial, and subtracted the latter from the former (i.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Egner, Ely, and Grinband (2010;see also, Egner, 2011;Egner, Etkin, Gale, & Hirsch, 2008;Egner & Hirsch, 2005;Etkin, Egner, Peraza, Kandel, & Hirsch, 2006) gave participants a two-choice gender task in which they had to decide whether a facial picture was male or female. The distracting word "male" or "female" was presented overtop of the picture, thus creating congruent trials (i.e., when the picture and word were the same gender) and incongruent trials (i.e., when the picture and word were different genders).…”
Section: Grattonmentioning
confidence: 99%